Cleavage of silicon by laser-based shock waves: interpretation by nanoscopic length scales - Hess, Peter; Lomonosov, Alexey M. (Applied surface science, 2014)
Cleavage along the weakest Si{111} cleavage plane is measured by impulsive fracture using surface acoustic waves (SAWs) with steep shock fronts, generated by pulsed laser irradiation and recorded with a laser probe-beam-deflection setup. The theoretical cleavage strength, obtained by ab initio calculations for perfect single-crystal silicon lattices is compared with the strength resulting from an improved Polanyi-Orowan cleavage model. The critical strength of a real silicon crystal, measured by using calibrated elastic surface pulses with shocks, was employed to extract the corresponding critical length scale characterizing the cleavage process on the basis of the modified cleavage model. The extracted length scale of 7nm can be connected with the size of the microstructural defect initiating failure. Usually stress generating surface defects are responsible for the nucleation of brittle fracture, especially in nanoscale systems with large surface areas.